Epidemiological analysis of progression-free survival (PFS) and overall survival (OS) in non-small-cell lung cancer patients in Republic of Macedonia - Risteski, Milan; Crvenkova, Simonida; Atanasov, Zoran; Isjanovska, Rozalinda (My University, 2013)
Lung cancer represents the leading cause of cancer mortality worldwide, accounting for ~1.2 million deaths each year. Improving survival in lung cancer is a major challenge for modern oncology considering that 5-year survival remains < 15%, across all stages of the disease with < 7% of patients alive 10 years after diagnosis. About 85% to 90% of lung cancers are non-small-cell lung cancer (NSCLC). Lung cancer is the leading cause of cancer-related mortality in Macedonia with more than 900 newly diagnosed lung cancer patients per year. The motive for undertaking the study was precisely the lack of adequate statistical data on treatment outcomes and survival rates of non-smal-cell lung cancer patients in the country. The main goal was to provide an assessment of progression-free survival and overall survival in NSCLC patients treated at UCRO-Skopje, over the past three years: 2009-2011. The research represents a follow-up study. The study was based on filling in forms for an epidemiological analysis of PFS and OS in NSCLC patients. These forms contain demographic, clinical and histological data, as well as dates of diagnosis, treatment initiation and outcomes. Data were collected from patient files for a period of three years (2009-2011), collected through the registration of each NSCLC patient treated in the period of the investigation. The statistical series were analysed by determining the ratio, proportions, chi-square and Student t-test and survival analysis. The study included 1002 patients with NSCLC treated at the UCRO, of whom 859 were males and 137 were females, and 0.6% missing data for gender. The average age of patients was 60.4 ± 9.0 y., min. of 19 y., max. of 85 y. Most of the patients were smokers- 86.9%. The dominant stage in NSCLC was stage IV, with 36.3%, followed by IIIA 17.5%, stages IIIB and IIB with 13.6% and so on. In the examined group of patients the most common subtype was 56.9% with planocellular, 28.2% with adenocarcinoma, large-cell with 7.7% and missing / no closer subtype 7.2%. Median survival from diagnosis to the last check-up/death was 6.2 m. 25% of patients with NSCLC from diagnosis to the last check-up/death died in the first 2.5 m and 25% survived more than 11.1 m. Median survival from treatment outset to the last check-up/death was 5.4 m. 25% of patients with NSCLC survived for two months from the outset of treatment to the last check-up/death and 25% survived for more than 10.8 m. In the course of the study we found that the median survival in 2009, 2010 and 2011 differed from the diagnosis to the last control/death. In 2009, median survival was 7.5 m and we registered a statistically significantly longer survival compared to 2010 - 6.1 m, and 2011 - 5.4 m. Similar data and conclusions were received in calculating the survival from therapy to the last check-up/death. Median survival in 2009 was 6.2 m and this is a statistically significant longer survival compared with 2010 (5.9 m) and 2011 (4.6 m). The results indicate that compared with international data patients with NSCLC had a shorter life of survival.We hope that this study will help to improve the future treatment of non-small-cell lung cancer patients through optimizing the treatment for every single patient, which will help in longer patient survival. Precise determination of these data provides for a proper selection of the best treatment option and optimized therapy for every patient.